The structure of {[Co(pht)(bpy)(H2O)]·3H2O}n (pht is phthalate and bpy is 4,4'-bipyridine) and the role of solvent water clusters in structure stability - Harvey, Miguel Angel (2014)
The CoII cation in poly[[aqua(-benzene-1,2-dicarboxylato3 O1 ,O2 :O1 )(-4,40 -bipyridine-2 N:N0 )cobalt(II)] trihydrate], {[Co(C8H4O4)(C10H8N2)(H2O)]3H2O}n, is octahedrally coordinated by two N atoms of two 4,40 -bipyridine ligands, three O atoms from phthalate anions and a fourth O atom from a coordinated water molecule. The packing consists of planes of coordination polymers linked by hydrogen bonds mediated by three solvent water molecules; the linkage is achieved by the water molecules forming intricate oligomeric clusters which also involve the O atoms of the phthalate ligands.